Plazma Destekli Kimyasal Buhar Biriktirme Yöntemi İle Tantal Katkılı Elmas Benzeri Karbon Film Üretimi Ve Karakterizasyonu - Orhon, Nilüfer (Fen Bilimleri Enstitüsü, 2012)
Bu çalışmada manyetik alan sıçratma ve plazma destekli kimyasal buhar biriktirme sistemi ile tantal katkılı elmas benzeri karbon ince film üretimi, üretim parametrelerinin optimizasyonu ve filmlerin karakterizasyonu amaçlanmıştır. Bu sistemde temel özellik kaplama sıcaklığının düşük olmasıdır. Altlık malzemesi olarak tek kristal silisyum plaka veya paslanmaz çelik numuneler üzerine öncelikle 2 dk süreyle metalik Ta kaplanmış, üzerine a-C:H yapısı büyütülmeye çalışılmıştır. Metalik Ta kaplanmasının nedeni filmin yüzeye tutunmasını iyileştirmektir. Kaplama parametrelerinin optimizasyonu için basınç, bias potansiyeli, katot gücü, gaz akış oranı, kaplama süresi gibi temel değişkenlerin etkileri incelenmiştir. Yapılan kaplamaların faz analizi için X-ışını difraktometresi, kalınlık ve yapı analizi için taramalı elektron mikroskobu, yapıdaki karbon atomlarının bağ yapılarını belirlemek için de Raman spektrometresi yöntemleri kullanılmıştır. Karakterizasyon sonucunda karbür fazının oluşumu için en iyi katot gücünün 0,2 kW, fakat katot zehirlenmesinin önüne geçmek için kullanılması gereken güç değerinin 0,3 kW olduğu belirlenmiştir. Kaplama basıncı olarak 0,5 Pa, gaz akış oranı CH4/Ar ≈ 1 ve kaplama süresi 1 sa olarak optimize edilmiştir. 350 V bias potansiyelinde daha kalın bir kaplama elde edilmiştir. Tüm incelemeler sonucunda en büyük problem katot zehirlenmesi, dolayısıyla kaplama homojenizasyonunun sağlanamaması olmuştur.

Diamond-like carbon films is a metastable form of amorphous carbon structure that containing significant amounts of sp3 bond. Diamond like carbon is a wide band gap semiconductor with a high mechanical hardness, chemical stability and optical transmittance. Diamond-like carbon films are widely used as a protective coating of the optical windows, magnetic storage discs, car parts, biomedical coatings and micro-electro mechanic storage discs. Tantalum is a very hard, malleable, ductile and quite heavy transition metal. Tantalum is a very heavy silvery white highly refractory metal. Its heaviness is not only an enabling factor in its concentration from the cassiterite-bearing sands, but also in some industrial applications. Tantalum carbide is one of the hardest substances known and it is used in tools for cutting very hard metals and alloys. Hardness and high melting point makes it suitable for making high temperature dies in combination. In this study, to take advantage of tantalum and tantalum carbide because of good wear characteristic were used for doping in diamond-like carbon films. Variety of materials derived from carbon films for replacement and improvement of properties of diamond-like carbon films. These materials are similar to diamond-like carbon film structure, but also may contain metal atoms (Me-DLC) in addition to carbon and hydrogen. Many modifications to the diamond-like carbon films, is to reduce the high internal stress of diamond-like carbon films of by lowering the already low friction coefficient in order to reduce the surface energies. The objectives of this study are; the production of tantalum doped diamond-like carbon thin films in a magnetron based plasma assisted chemical vapor deposition system, characterization of these films and the optimization of production parameters. Sputtering and doping of the metal into the a-C:H structure within the system was intended. Observation of carbide formation, and its effects on the mechanical and tribological properties of the films was aimed. The key feature of this system is very low coating temperatures. Therefore, this system is very suitable for polymer-like coatings. DLC has very good wear resistance and low friction coefficient. It was proposed that doping of tantalum into DLC may further improve wear behaviors of the structure due to the known wear resistance enhancing effects of tantalum. In experiments, single crystal silicon wafer and stainless steel substrates were used. Prior to loading the substrate into the deposition chamber, the substrate was cleaned in ultrasonic cleaner with acetone for duration of 10 min. The substrate piece was cleaned with alcohol, air dried and placed in the deposition chamber. The samples were placed in front of the target, in an upright position on the anode. The distance between the cathode and the sample was determined as 9 cm. The samples were subjected to atomic sized final cleaning with glow discharge in chamber. Plasma was generated with argon gas at 5 Pa chamber pressure for duration of 10 min. Bias voltage was 650 V, frequency was 150 kHz, argon gas flow was 65 sccm used for the formation of plasma, respectively. Metallic tantalum was coated on the samples for 2 minutes and a-C:H structure was tried to be grew on the metallic tantalum film. The reason of the coating metallic tantalum on the surface was to improve the adherence to DLC structure. Ta doped DLC films were then produced with previously optimized parameters .The basic variables such as bias potential, target power, gas flow rate; deposition time and pressure to optimize coating parameters were investigated. X-ray diffractometer was used for the phase analysis of the coatings. Cu-Kα radiation that produced in 40 kV and 40 mA was used for the determination of phase. θ=2° scanning angle was chosen and scans were carried out between 20°-120°. All diffractograms were normalized according to the highest violence in this study and qualitative information was obtained about the rate of the phases. Thickness measurements were taken with the cross-sectional view by scanning electron microscopy and EDS analysis was performed from the cross-sectional view for elemental content analysis. Accelerating voltage was chosen during EDS analyzes of the 10 kV, for cross sectional views 5 kV. Raman spectroscopy was used to analyze the carbon bonds in DLC films. HeNe laser source was used, working with power 17mW. 632,817 nm wavelength used in the analysis and were screened between the wavelengths of 400-2000 cm-1. All analyzes were taken 3x3 mode and this mode has been sufficient for the appearance of the expected peaks. 10X magnification of the lens on the device that options were chosen. Berkovich nanoindenter was used to determine the mechanical properties. 5 mN forces were used for each test during analysis. Each sample was measured over 20 points and the average results were evaluated. Elasticity modulus of the films as a result of the hardness tests was examined. Ball on disc tribometer method was used to determine to wear properties. Tribology test using stainless steel balls were made in dry conditions on the stainless steel samples. 4 mm radius of gyration, 5 cm/s rotation speed and 4 N loads were used during the test. One of the most important parameters affecting the coating structure is the ratio of argon/methane and the appropriate coatings can be obtained when this ratio is approximately equal to 1. Increases the amount of methane is observed cathode poisoning and decreases the amount of methane is observed in the metallic coating. Decomposition in the plasma and the formed homogeneous coatings provided the best way, the pressure value determined to 0.5 Pa. Over this pressure value, amount of carbon reduces in the structure. Increase the potential of bias reduces the amount of tantalum in the structure. Therefore, decreasing the formation of tantalum carbide, declining rate of crystallization and more graphitic structure was observed. Accordingly, it is preferred to be 350 V bias potential. The amount of power applied to magnetron, understood that a precise position for the problem of the cathode poisoning. Tantalum carbide structure clearly not been seen in samples coated with 0.3 kW and sufficiently Ta is not sputtered with 0.2 kW because of cathode poisoning. Using different power units is thought to be achieved optimization with scanning range in these two values. Optimum coating time is observed for 1 hour. Again, because of the forming nonconductive layer on the cathode, the coating is weakened or stopped for a while after the plasma is considered and as a result of this is thought to decrease the deposition rate. 2 and 4 hours no difference in the thickness of coatings also provides support to this idea. As a result of the measurement of mechanical properties, Vickers hardness ranged from 797-928 in structures containing tantalum carbide. Other structures were measured the average hardness of 650 Vickers. Understood that the forming of tantalum carbide is increases the hardness. Result of the hardness tests, modulus of elasticity values were measured between 88-105 GPa. In the literature, diamond-like carbon film is given lower elasticity modulus. Accordingly, the addition of tantalum in diamond-like carbon film to increase the modulus of elasticity and thus can be said to reduce the elastic feature. Compared to modulus of elasticity, moduli of elasticity of structures including tantalum carbide are higher than others. Had a negative effect on the elastic properties can be proposed that the formation of tantalum carbide. Tribological analysis result, coefficient of friction of the a-C:H structure including tantalum was determined as 0.1. As a result of all investigations, the biggest problem was cathode poisoning, therefore, been of making a homogeneous coating.
Production Of Tantalum Doped Diamond-like Carbon Film By Means Of Plasma Assisted Chemical Vapor Deposition And Its Characterisation
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: plazma destekli kimyasal buhar biriktirme; elmas benzeri karbon; tantal; plasma assisted chemical vapor deposition; diamond like carbon; tantalum